Mobile application for control and management of citizen security - Alejandro Boza-Chua; Laberiano Andrade-Arenas; Avid Roman-Gonzalez (Institute of Advanced Engineering and Science, 2023)
Currently, Peru is one of the countries with the highest levels of citizen insecurity in Latin America, and its capital is considered the thirtieth most populated city in the world, thus being one of its territories with the highest percentage of citizen insecurity, providing a poor quality of life to its citizens as they feel unsafe when passing through different places and being victims of any criminal act. Therefore, this research work is developed to support this problem through the implementation of a mobile application that manages and controls citizen insecurity. Applying the research method based on design and scrum methodology, which together generate greater control over changes during project development. In addition, resources and the support of different tools were used for its study and execution, such as marvelApp for the design and prototyping of the mobile application and android studio. Obtaining highly viable results for the support of citizen security through a suitable and fully viable mobile application.